Concrete thermal energy storage for linear Fresnel collectors: Exploiting the South Mediterranean's solar potential for agri-food processes. (15th June 2018) - Buscemi, A.; Panno, D.; Ciulla, G.; Beccali, M.; Lo Brano, V.
Highlights: Use of thermal energy generated by a Concentrated Solar Heating Industrial plant. Integration of solar thermal energy into a pasta factory in Southern Italy. Innovative layout with a concrete heat storage volume and Linear Fresnel Collectors. A TRNSYS model has been developed to optimize the design of solar collectors and the storage. The maximum affordable specific cost of the solar field was identified. Abstract: Italy is celebrated in the world for its agri-food industries while the process of production of pasta is highly energy demanding and requires both electrical and thermal energy simultaneously. Because most of the Italian factories producing pasta are located in the Southern part of the country, the direct use of thermal energy generated from the sun would be particularly profitable. In this study, the authors examine the possibility of generating by a Solar Industrial Process Heating plant the thermal energy required annually by an existing factory that produces durum wheat pasta located in Sicily (Italy). The hypothesized plant scheme consists of an array of Fresnel linear solar collectors and a concrete thermal energy storage system in which a heat transfer diathermal fluid circulates. This particular combination, although not the most efficient from the thermodynamic point of view, determines a lower visual impact and easier maintenance during the life span of the system. The use of food graded thermal oil ensures a high level of safety. A TRNSYS model has been developed in order to simulate the energy performance of the above described plant with the aim of optimizing the design of the solar heat for industrial process systems in terms of solar collectors and thermal energy storage dimensions taking into account the available space in the specific location. The obtained results show that the direct use of the thermal energy generated with the Fresnel solar collectors can significantly contribute to increase the sustainability of the most thermal energy-demanding factories working in the food industry, a strategic sector in the Mediterranean Area. The average annual solar contribution can reach about 40% of the total thermal energy requirement, maximizing the solar energy production during the summer season. Moreover, the proposed study allowed the determination of the maximum investment cost of the plant linked to a simple payback time, without external incentives, of 8 years.